2020
DOI: 10.3389/fphys.2020.00577
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-D-Aspartate Receptors in Hematopoietic Cells: What Have We Learned?

Abstract: also contributed to the review process for this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Moreover, NMDA receptors in mature erythrocytes may affect the life span of erythrocytes. In mature human and rat erythrocytes, NMDA receptors impact cellular nitric oxide synthase activity [ 9 , 20 ]. It is possible that altered NMDA receptor function affects the life span of erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, NMDA receptors in mature erythrocytes may affect the life span of erythrocytes. In mature human and rat erythrocytes, NMDA receptors impact cellular nitric oxide synthase activity [ 9 , 20 ]. It is possible that altered NMDA receptor function affects the life span of erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent studies revealed that NMDA receptors play significant roles in hematopoiesis [ 9 ]. NMDA receptor subunits are expressed in megakaryocytes and erythroid cells and function as ion channels, similar to their neuronal counterparts [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to cilia-associated genes, the most significant variable in our model was a region of GRIN2C, an NMDA receptor that may have effects on hematopoietic differentiation by controlling calcium homeostasis in differentiating cells [81] , [82] . Although the full structure and function of this gene has yet to be elucidated, we identified a narrow 50-basepair region in GRIN2C’s N-terminal extracellular domain that is significantly associated with accelerated relapse in high-risk pediatric B-ALL patients.…”
Section: Discussionmentioning
confidence: 99%